Model pembelajaran scaffolding berbantuan augmented reality untuk meningkatkan keterampilan kognitif siswa - Farrel Rahma Aliyya; Asep Wahyudin; Rani Megasari Megasari (Universitas Pendidikan Indonesia, 2026)
Students' cognitive abilities are crucial for developing higher-order thinking skills, including the ability to analyze, evaluate, and solve problems. However, Indonesia ranked 66th out of 81 countries in the 2022 Programme for International Student Assessment (PISA). Therefore, efforts to improve students' cognitive abilities are essential. This study aimed to develop and evaluate an Augmented Reality (AR)-assisted scaffolding learning model to enhance students' cognitive abilities in computer systems learning. The RnD method was employed with the ADDIE model. The study was conducted at SMA Negeri 2 Bandung and involved 30 students. Data collection was conducted using a one-group pretest-posttest design. The results showed a significant increase in students' cognitive achievement among those who attended classes using the AR-assisted scaffolding learning model. Student responses to this learning model were categorized as